The role of Pharmaceutical Marketing in Prescribing Decisions in a Developing Country: A Comprehensive Study Exploiting Theory of Planned Behaviour - Al-Areefi, Mahmoud; Mohamed Ibrahim, Mohamed Izham; Abubakr Abdelraouf Alfadl (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Background: Prescription medicines have become a major component of health systems in both developed and developing countries contributing to, may be, more than half of the total health care expenditure in the developing countries. Although literature directly attributing rise in medicines expenditure to prescribers’ decision, but still only a few researches had employed studies with sound theoretical foundations to comprehensively examine prescribing decision behaviours. Our objective was to investigate potentially modifiable factors, which may influence prescribing decisions of physicians employing theory of planned behaviour. Method: A quantitative survey approach was used to investigate the proposed hypotheses. Population was physicians in outpatient clinics in both private and governmental hospitals in Sana’a, capital city of Yemen. A structured questionnaire was designed to measure the influence of drug-promoting marketing techniques on physicians’ prescribing decisions. Data was collected through an anonymous survey questionnaire. The hypotheses were tested by multiple regressions analysis. Ethical approval was obtained from the Ethical Committee of the Ministry of Public Health and Population (MoPHP), and participants provided written consent before enrolling in the study. Result: Physicians admitted the presence of promotional influence on their prescribing decision. The study revealed that receiving low-value promotional items, belief of physicians that it is appropriate to accept both low- and high-value promotional items, physicians’ exposure to company-direct sources of information, and drug promotion-related factor all are positively and significantly related to physicians’ prescribing decisions (? = 0.438, p <0.001; ? = 0.089, p =0.027; ? = 0.157, p <0.001; ? = 0.093, p =0.032; and ?= 0.118, p = 0.007 respectively). Conclusion: This research clarified the role played by pharmaceutical companies to influence prescribing decisions of physicians. Therefore, could provide theoretical framework for policymakers in Yemen, and other countries with similar conditions, to develop a suitable policy and strategy in terms of drug promotion.